No Gut No Gain! Enteral Bile Acid Treatment Preserves Gut Growth but Not Parenteral Nutrition–Associated Liver Injury in a Novel Extensive Short Bowel Animal Model. Issue 8 (27th April 2018) - Villalona, Gustavo; Price, Amber; Blomenkamp, Keith; Manithody, Chandrashekhara; Saxena, Saurabh; Ratchford, Thomas; Westrich, Matthew; Kakarla, Vindhya; Pochampally, Shruthika; Phillips, William; Heafner, Nicole; Korremla, Niraja; et al.
Abstract: Background: Parenteral nutrition (PN) provides nutrition intravenously; however, this life‐saving therapy is associated with significant liver disease. Recent evidence indicates improvement in PN‐associated injury in animals with intact gut treated with enteral bile acid (BA), chenodeoxycholic acid (CDCA), and a gut farnesoid X receptor (FXR) agonist, which drives the gut–liver cross talk (GLCT). We hypothesized that similar improvement could be translated in animals with short bowel syndrome (SBS). Methods: Using piglets, we developed a novel 90% gut‐resected SBS model. Fifteen SBS piglets receiving PN were given CDCA or control (vehicle control) for 2 weeks. Tissue and serum were analyzed posteuthanasia. Results: CDCA increased gut FXR (quantitative polymerase chain reaction; P = .008), but not downstream FXR targets. No difference in gut fibroblast growth factor 19 (FGF19; P = .28) or hepatic FXR ( P = .75), FGF19 ( P = .86), FGFR4 ( P = .53), or Cholesterol 7 α‐hydroxylase ( P = .61) was noted. PN resulted in cholestasis; however, no improvement was noted with CDCA. Hepatic fibrosis or immunostaining for Ki67, CD3, or Cytokeratin 7 was not different with CDCA. PN resulted in gut atrophy. CDCA preserved ( P = .04 vs control) gut mass and villous/crypt ratio. The median (interquartile range) for gut mass for control was 0.28 (0.17–0.34) and for CDCA was 0.33 (0.26–0.46). Conclusions: We note that, unlike in animals with intact gut, in an SBS animal model there is inadequate CDCA‐induced activation of gut‐derived signaling to cause liver improvement. Thus, it appears that activation of GLCT is critically dependent on the presence of adequate gut. This is clinically relevant because it suggests that BA therapy may not be as effective for patients with SBS.